Perkawinan Campuran Menurut Gereja Katolik: Tantangan dan Solusi dalam Konteks Pluralisme di Indonesia - Caroline Resthy Wardhani Halawa; Naya Aurora Smith (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This article discusses the challenges and solutions related to mixed marriages according to the Catholic Church in the context of pluralism in Indonesia, a multicultural society with diverse religions. In the modern world, mixed marriages are increasingly common but remain controversial, often posing a dilemma between maintaining religious values and accepting modernity. The Catholic Church views marriage as a holy sacrament that requires a unity of faith between the couple. However, in practice, many Catholics marry non-Catholics, which can lead to struggles in building the foundation of faith in the family, especially the direction of children's faith education. This article also explains the importance of a pastoral approach to support couples in mixed marriages in facing this challenge. The research uses the literature study method in the hope of providing insights and solutions that are relevant for mixed marriage couples in the current era.